Condom use during commercial sex among clients of Hijra sex workers in Karachi, Pakistan (cross-sectional study). Issue 2 (30th September 2011) - Siddiqui, Anees ur Rehman; Qian, Han-Zhu; Altaf, Arshad; Cassell, Holly; Shah, Sharaf Ali; Vermund, Sten H
Abstract : Objective: To describe the prevalence and predictors of condom use and sexual risk in the male clients of Hijra sex workers (HSWs) in Karachi, Pakistan. Design: Cross-sectional study. Setting: Karachi, Pakistan. Participants: Clients of HSWs were recruited with assistance from HSWs and a non-governmental organisation (NGO) focused on men who have sex with men (MSM) during October–November 2010. Measurements: The interviewer administered the questionnaire to each participant to solicit information on demographics, HIV/AIDS knowledge/attitudes and sexual risk behaviours/practices, including condom use in the last sexual act with the HSW. Results: Of the 203 participants, 42.4% reported that they used condoms during their last sexual act with HSW, 40% were married, 18% had ever used drugs or alcohol, and 52% reported also engaging with female sex workers in the last month. Casual HSW clients were more likely to use condoms than regular clients (adjusted OR (AOR), 2.50; 95% CI 1.34 to 4.65), as were persons with a higher education level (AOR 5.8; 95% CI 1.6 to 20.3). Drug/alcohol users and non-users were equally likely to use condoms (AOR 1.11; 95% CI 0.51 to 2.24). Conclusion: Clients of HSWs in Pakistan are at risk of acquiring HIV/STI infections. Concerted efforts are needed to increase condom use in this key bridge population to curtail the spread of HIV in the general population.